Persepsi Peternak Sapi Potong Terhadap Sistem Integrasi Sapi-Sawit Di Kecamatan Kumpeh Ulu Kabupaten Muaro Jambi - Arya Gustian Jaya; Afriani Harahap; Eko Wiyanto (Jurnal Ilmu Peternakan Indonesia, 2026)
This study aims to determine the perception level of beef cattle farmers toward the cattle-oil palm integration system and to analyze the factors influencing this perception in Kumpeh Ulu District, Muaro Jambi Regency. The method employed was a survey method, utilizing purposive sampling for both sample selection and village determination, with a total of 51 respondents. The data consisted of primary and secondary data, which were analyzed using descriptive analysis and multiple linear regression. The results indicated that the farmers' perception level toward the cattle-oil palm integration system fell into the "fairly good" category, with an average score of 54.67%. The regression analysis revealed a coefficient of determination ($R^2$) of 0.238, meaning that 23.8% of the farmers' perception could be explained by the variables of age, education level, farming experience, livestock population, and land area, while the remaining percentage was influenced by other factors outside the model. The simultaneous test (F-test) showed that all independent variables collectively had a significant effect, with a p-value of 0.027. However, the partial test (t-test) demonstrated that only the education level variable had a significant effect, with a p-value of 0.016. In conclusion, the farmers' perception toward the cattle-oil palm integration system is considered fairly good, and the key factor influencing this perception is their education level.